Pregnancy complicated by myoma: a case report - Dulewad, S. S.; Temurkar, Shraddha; Satpute, Kajol (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Leiomyomas are the most common benign tumor of the uterus and affects 40% to 50% of women. Most of them are asymptomatic (70-80%) but 5% are symptomatic. Fibroid in pregnancy affects its outcomes. Fibroid in pregnancy can be managed conservatively or surgically in the form of myomectomy or hysterectomy. Fibroids when present are associated with complications in 10-40% of pregnant patients like abdominal pain, spontaneous abortion etc.